Exploring Muslim Consumers’ Perceptions of Halal-Certified MSME Food: Evidence from “Kebab Rakyat” in Surabaya - Keisya Az Zahra Laetisya Virdian; Yan Putra Timur (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
Indonesia ranks among the countries with the highest halal product consumption in the world, yet the competitiveness of its national halal industry in the food sector remains below that of Malaysia and the United Arab Emirates. This condition indicates that halal certification has not been fully optimized as a business strategy, particularly at the micro, small, and medium enterprise (MSME) level. This study aims to explore Muslim consumer perceptions toward Kebab Rakyat, a halal-certified food MSME in Surabaya. Through a descriptive qualitative methodology, this study integrates data from multiple sources via interviews, observation, and documentation. The findings reveal a collective understanding among Muslim consumers that halal certification serves as a form of consumer protection. However, variations in perception were observed regarding its significance, where some consumers regarded halal certification as a primary consideration in purchase decisions, while others viewed it as a supporting factor complementing aspects such as taste, price, and consumption experience. This study contributes to advancing understanding of the role of halal certification in shaping positive perceptions, enhancing consumer confidence, and strengthening trust toward halal food MSMEs.